Geopolymer repairing material for concrete structure and repairing method of geopolymer repairing material

By using alkali-activated slag fly ash geopolymer repair materials, combined with manual chiseling, the problem of low interface strength and poor durability in concrete structure repairs in the existing technology has been solved, and an efficient and long-lasting repair effect has been achieved, with the advantages of Environmentally friendly advantages.

CN119349941AInactive Publication Date: 2025-01-24CHINA UNIV OF MINING & TECH (BEIJING) +1
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411501181.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-25
Publication Date
2025-01-24
Estimated Expiration
Not applicable · inactive patent

AI Technical Summary

Technical Problem

In the existing concrete structure repair methods, the bonding interface between new and old concrete is low, has poor durability, and the commonly used repair materials are not compatible with old concrete, which can easily lead to chemical reactions and the generation of 'traumatic surfaces', resulting in the lack of long-lasting repair effect.

Method used

The use of alkali stimulation of slag flour ash as a repair material, and prepare raw materials such as sand, stones, slag, flour ash, water glass, and sodium hydroxide through a specific proportion, forming alkali to stimulate the repair material of the geological polymer of the slag flour ash, and repair the repair During the process, manual rules are carried out.

Benefits of technology

It significantly improves the split resistance of the repair interface and the penetration of the chloride ion ion, enhances the compatibility with the old concrete, extends the durability of the repair effect, reduces the use of cement, and reduces carbon emissions.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119349941A_ABST
    Figure CN119349941A_ABST
Patent Text Reader

Abstract

The invention discloses a geopolymer repairing material for a concrete structure and a repairing method thereof. The repairing method comprises the following steps: preparing the geopolymer repairing material for the concrete structure; the interface of the concrete to be repaired is subjected to manual regular scabbling treatment, and a target repairing interface is determined; and the repairing material is applied to the target repairing interface, so that the to-be-repaired concrete is repaired. The repairing material has the characteristics of mild activity, good compatibility with old concrete of an existing structure, high interface splitting tensile strength after repairing, good chloride ion permeability resistance and the like, and the splitting tensile strength and the chloride ion permeability resistance are improved compared with those of repairing by using common concrete; the splitting tensile strength is improved, and the chloride ion penetration resistance is remarkably improved. The concrete repairing agent can be widely used for repairing concrete and has popularization and application prospects. And meanwhile, the slag fly ash is reutilized, so that the method has important significance for reducing the use of cement, reducing carbon emission and protecting the environment.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of repairing concrete building structures, and in particular to a geopolymer repairing material for a concrete structure and a repairing method thereof. Background Art

[0002] Many concrete structures are facing repairs nowadays. However, the bonding area between the repair material and the old concrete is a weak area in the structure, which is related to the long-term performance of the entire structure. Water leakage and steel corrosion that occur during the use of concrete structures are often related to the bonding surface between the new and old concrete. At present, the conventional repair method is to use a higher grade of concrete for repair as recommended by the specification, but many actual engineering practices have shown that the strength of the bonding interface between the new and old concrete repaired by conventional maintenance methods is low, the durability is poor, and the interface between the new and old concrete is easy to separate; and some highly active organic chemical gelling agents are used for some leakage repairs. This type of repair gelling agent is usually not compatible with the old concrete, and a violent chemical reaction will occur to generate a new "wound surface", and the repair effect is often not long-lasting. Therefore, a new repair material and repair method are needed to solve the problems of low bonding interface strength, poor durability and poor effect in the existing technology. Summary of the invention

[0003] In view of this, an embodiment of the present invention provides a geopolymer repair material for a concrete structure and a repair method thereof, which solves the problems of low bonding interface strength, poor durability and poor effect of the existing method.

[0004] According to a first aspect, an embodiment of the present invention provides a geopolymer repair material for a concrete structure, wherein the repair material is alkali-activated slag fly ash.

[0005] The raw materials include: sand, gravel, alkali activator, slag, fly ash, water, and each raw material is prepared according to weight to determine the alkali activated slag fly ash.

[0006] In combination with the first aspect, in a first embodiment of the first aspect, the alkaline activator consists of water glass and sodium hydroxide.

[0007] In combination with the first embodiment of the first aspect, in the second embodiment of the first aspect, the modulus of the alkaline activator is 1.3, and the specific preparation ratio is: 147.2 parts of the water glass and 23.9 parts of the sodium hydroxide.

[0008] In combination with the first embodiment of the first aspect, in the third embodiment of the first aspect, the raw materials are prepared by weight to determine the alkali-activated slag fly ash, including:

[0009] The alkali-activated slag fly ash is prepared in the proportion of 520 parts of sand, 965.5 parts of gravel, 250 parts of slag, 250 parts of fly ash, 147.2 parts of water glass, 23.9 parts of sodium hydroxide and 104.5 parts of water to improve the splitting tensile strength of the repair interface.

[0010] The geopolymer repair material for concrete structure provided by the embodiment of the present invention has the characteristics of mild activity of the repair material, good compatibility with the old concrete of the existing structure, high splitting tensile strength, good resistance to chloride ion penetration, etc. The splitting tensile strength and resistance to chloride ion penetration are both improved compared with the higher grade ordinary concrete repair recommended by the specification, and can be widely used for concrete repair, with promotion and application prospects. At the same time, slag fly ash is also reused, which is of great significance for reducing the use of cement, reducing carbon emissions and protecting the environment.

[0011] According to a second aspect, a method for repairing a geopolymer repair material for a concrete structure provided by an embodiment of the present invention comprises:

[0012] Prepare a geopolymer repair material for a concrete structure according to any one of the embodiments of the first aspect of this example;

[0013] Perform artificial regular roughening on the interface of the concrete to be repaired to determine the target repair interface;

[0014] The repair material is applied at the target repair interface to repair the concrete to be repaired.

[0015] In combination with the second aspect, in the first implementation of the second aspect, before roughening the interface of the concrete to be repaired, the method further includes: preparing the alkali activator in the repair material 24 hours in advance.

[0016] In combination with the second aspect, in the second embodiment of the second aspect, the artificial regular roughening process is artificial roughening until the coarse aggregate is exposed, and the depth is about 1 / 3 of its diameter.

[0017] In combination with the second aspect, in a third embodiment of the second aspect, after roughening the interface of the concrete to be repaired, the method further includes: fully washing the roughened interface with water to determine the target repair interface.

[0018] The repair method of the geopolymer repair material for concrete structure provided in this embodiment has the characteristics of mild activity of the repair material, good compatibility with the old concrete of the existing structure, high splitting tensile strength, good resistance to chloride ion penetration, etc. The splitting tensile strength and resistance to chloride ion penetration are both improved compared with the higher grade ordinary concrete repair recommended by the specification. At the same time, compared with the conventional non-treatment method, the roughening method improves the splitting tensile strength and significantly improves the resistance to chloride ion penetration. It can be widely used in the repair of concrete and has a prospect of promotion and application. At the same time, slag fly ash is also reused, which is of great significance for reducing the use of cement, reducing carbon emissions and protecting the environment.

[0019] According to a third aspect, an embodiment of the present invention provides an electronic device, comprising: a memory and a processor, wherein the memory and the processor are communicatively connected to each other, the memory stores computer instructions, and the processor executes the method for repairing a geopolymer repair material for a concrete structure described in the second aspect or any one of the embodiments of the second aspect by executing the computer instructions.

[0020] According to a fourth aspect, an embodiment of the present invention provides a computer-readable storage medium, wherein the computer-readable storage medium stores computer instructions, and the computer instructions are used to enable the computer to execute the method for repairing a geopolymer repair material for a concrete structure as described in the second aspect or any one of the embodiments of the second aspect. BRIEF DESCRIPTION OF THE DRAWINGS

[0021] In order to more clearly illustrate the specific implementation methods of the present invention or the technical solutions in the prior art, the drawings required for use in the specific implementation methods or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are some implementation methods of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative work.

[0022] Figure 1 is a schematic diagram of the microscopic morphology of the bonding surface of ordinary post-cast concrete according to an embodiment of the present invention;

[0023] Figure 2 is a schematic diagram of the microscopic morphology of the bonding surface of the alkali-activated slag fly ash post-cast concrete according to an embodiment of the present invention;

[0024] Figure 3 is a flow chart of a method for repairing a geopolymer repair material for a concrete structure according to an embodiment of the present invention;

[0025] Figure 4 It is a schematic diagram of the hardware structure of an electronic device provided by an embodiment of the present invention. DETAILED DESCRIPTION

[0026] In order to make the purpose, technical solution and advantages of the embodiments of the present invention clearer, the technical solution in the embodiments of the present invention will be clearly and completely described below in conjunction with the drawings in the embodiments of the present invention. Obviously, the described embodiments are part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by those skilled in the art without creative work are within the scope of protection of the present invention.

[0027] In this embodiment, a geopolymer repair material for a concrete structure is provided. The repair material is alkali-activated slag fly ash. The raw materials include: sand, gravel, alkali activator, slag, fly ash, and water. The raw materials are prepared by weight to determine the alkali-activated slag fly ash.

[0028] Specifically, the alkali activator is composed of water glass and sodium hydroxide. The preparation ratio of the alkali activator is: 147.2 parts of water glass and 23.9 parts of sodium hydroxide. According to the proportion of 520 parts of sand, 965.5 parts of gravel, 250 parts of slag, 250 parts of fly ash, 147.2 parts of water glass, 23.9 parts of sodium hydroxide and 104.5 parts of water, the alkali-activated slag fly ash is determined to improve the splitting tensile strength of the repair interface.

[0029] In a specific embodiment, the alkali activator solution is prepared by adding 23.9 parts of solid NaOH to 104.5 parts of water to prepare the NaOH solution, and then adjusting the modulus of the alkali activator to 1.3 by adding 147.2 parts of water glass. The preparation process of the alkali activator is to first put solid NaOH into a container, then slowly add water along the container wall and stir continuously to prepare a NaOH solution; and then adjust the modulus of the alkali activator to 1.3 by adding water glass. Before preparing geopolymer concrete, the alkali activator needs to be prepared 24 hours in advance.

[0030] As a further improvement of the present invention, 250 parts of slag and 250 parts of fly ash.

[0031] Regarding the composite ratio of the alkali activator, the present invention is obtained through exploratory test research on various ratios of water glass and sodium hydroxide. The test studies the effects of 5 different ratios on the splitting strength and anti-seepage performance of the repaired interface. The specific test ratio design is shown in the table below.

[0032] Table 1 Comparison of raw materials in different proportions

[0033]

[0034] The performance was measured by splitting tensile test and chloride ion penetration test, as shown in Table 2. The results show that the tensile strength of group A2 is the best, and the impermeability of group A3 is the best. Therefore, considering the tensile and impermeability performances, the optimal ratio of the activator should be between A2 and A3. Therefore, the present invention further conducted preliminary tests to adjust the ratio of the activator, and found that when water glass: sodium hydroxide: water = 147.2: 23.9: 104.5, the splitting tensile strength was 1.52 and the permeability coefficient was 1.05, both of which exceeded A2 and A3 (see Tables 3 and 4 below for specific results).

[0035] Table 2 Comparison of splitting tensile test and chloride ion penetration test performance

[0036] Test results A1 A2 A3 A4 A5 Splitting tensile strength / MPa 0.89 1.19 1.02 0.82 0.53 <![CDATA[Ionic permeability coefficient / × 10 -11 m 2 / s]]> 5.08 3.03 1.70 2.76 2.95

[0037] Regarding the ratio of slag to fly ash, the present invention is obtained through exploratory test research on a variety of different ratios of slag to fly ash. The test studies the effects of 5 different ratios on the splitting strength and impermeability of the repaired interface. The specific test ratio design is shown in the table below.

[0038] Table 3 Second comparison table of raw materials with different proportions

[0039]

[0040] The properties were measured by splitting tensile test and chloride ion penetration test, as shown in Table 4.

[0041] Table 4 The second comparison table of splitting tensile test and chloride ion penetration test performance

[0042] Test results C40 S0 S30 S50 S70 S100 Splitting tensile strength / MPa 0.98 0.85 1.18 1.52 1.34 1.19 <![CDATA[Ionic permeability coefficient / × 10 -11 m 2 / s]]> 1.17 1.76 1.39 1.05 1.23 1.35

[0043] It can be concluded that when the slag content is 250 parts, the repair material has the best performance. The measured splitting tensile strength of the repair interface can reach 1.52MPa, and the chloride ion permeability coefficient is 1.05×10 -11 m 2 / s. This is much better than the conventional repair effect of ordinary concrete (C40) (its splitting tensile strength is only 0.98MPa and the chloride ion permeability coefficient is 1.84×10 -11 m 2 / s).

[0044] In this embodiment Figure 1 The scanning electron microscope image of the repair interface area of ​​a higher grade of ordinary concrete, which is a conventional method recommended by the specification, clearly shows that the bonding surface is not firm and dense, and has some defects and gaps. Figure 2 This is a scanning electron microscope image of the interface area of ​​slag fly ash geopolymer repair. It can be seen that the bonding surface area is relatively dense, with basically no cracks or voids. The hydration products of the repair material are evenly and densely bonded to the old concrete.

[0045] It can be seen that the alkali-activated slag fly ash geopolymer prepared by the present invention has the characteristics of high splitting tensile strength and good resistance to chloride ion penetration. The splitting tensile strength is 55% higher than that of ordinary concrete repair, and the resistance to chloride ion penetration is 17% higher.

[0046] The concrete structure geopolymer repair material provided by the embodiment of the present invention has the characteristics of mild activity, good compatibility with old concrete of existing structures, high splitting tensile strength, good resistance to chloride ion penetration, etc. The splitting tensile strength and resistance to chloride ion penetration are both improved compared with the higher grade ordinary concrete repair recommended by the specification, and can be widely used in the repair of concrete structures, with promotion and application prospects. At the same time, slag fly ash is also reused, which is of great significance for reducing the use of cement, reducing carbon emissions and protecting the environment.

[0047] In this embodiment, a method for repairing a concrete structure using a geopolymer repair material is provided, which can be used in electronic devices such as computers, mobile phones, tablet computers, etc. Figure 3 Schematic diagram of a geopolymer repair material for a concrete structure according to an embodiment of the present invention. Figure 3 As shown, the process includes the following steps:

[0048] S11, prepare the geopolymer repair material of the concrete structure as in the above embodiment. Prepare the repair material according to the fixed ratio and preparation requirements. The detailed information has been determined in the above embodiment and will not be repeated in this embodiment.

[0049] According to the above dosage specifications, slag fly ash, sand and gravel are taken out and fully mixed. When mixing the cementitious material and coarse and fine aggregates, the prepared alkali activator is added thereto according to the above dosage specifications and fully stirred, thereby preparing the alkali-activated slag fly ash geopolymer repair material. It should be noted that before preparing the geopolymer concrete, the alkali activator needs to be prepared 24 hours in advance.

[0050] S12, the interface of the concrete to be repaired is artificially roughened regularly to determine the target repair interface. The roughening depth range is such that the coarse aggregate is exposed. Specifically, the artificial roughening depth is controlled to expose the coarse aggregate to about 1 / 3 of its diameter.

[0051] In this embodiment, several common interface treatment methods are compared, namely conventional no treatment (the interface fracture surface is relatively smooth and flat, with only a little peeling at the edge), wire roughening (the concrete at the edge peels off more obviously, and the aggregate is slightly exposed in the middle of the cross section), artificial roughening (the coarse aggregate is exposed to about 1 / 3 of its diameter), and artificial splitting (the steel bar is completely exposed). The results are shown in Table 5:

[0052] Table 5 Performance comparison of different interface processing methods

[0053] Test results No interface processing Interface roughening Artificial roughening of the interface Artificial cleavage of interface Splitting tensile strength / MPa 1.52 1.60 1.71 1.63 <![CDATA[Ion permeability coefficient / × 10 -11 m 2 / s]]> 1.05 0.98 0.89 1.02

[0054] It can be seen that the best effect is achieved by artificial chiseling, which involves chiseling to expose the aggregate to about 1 / 3 of its diameter, washing the floating dust with water, and then pouring the repair material. The splitting tensile strength can reach 1.71 MPa, and the chloride ion permeability coefficient is only 0.89×10 -11 m 2 / s. Compared with no treatment, this roughening method increases the splitting tensile strength by 13% and the chloride ion penetration resistance by 15%.

[0055] S13, applying the repair material to the target repair interface to repair the concrete to be repaired.

[0056] The concrete structure geopolymer repair material and repair method provided in this embodiment have the characteristics of mild activity of the repair material, good compatibility with the old concrete of the existing structure, high splitting tensile strength, good resistance to chloride ion penetration, etc. The splitting tensile strength and resistance to chloride ion penetration are both improved compared with the higher grade ordinary concrete repair recommended by the specification. At the same time, compared with the conventional non-treatment method, the roughening method improves the splitting tensile strength and significantly improves the resistance to chloride ion penetration. It can be widely used in the repair of concrete and has a prospect of promotion and application. At the same time, slag fly ash is also reused, which is of great significance for reducing the use of cement, reducing carbon emissions and protecting the environment.

[0057] The present invention also provides an electronic device. Figure 4 , Figure 4 is a schematic diagram of the structure of an electronic device provided by an optional embodiment of the present invention, such as Figure 4 As shown, the electronic device may include: at least one processor 601, such as a CPU (Central Processing Unit), at least one communication interface 603, a memory 604, and at least one communication bus 602. The communication bus 602 is used to realize the connection and communication between these components. The communication interface 603 may include a display screen (Display), a keyboard (Keyboard), and the optional communication interface 603 may also include a standard wired interface and a wireless interface. The memory 604 may be a high-speed RAM memory (Random Access Memory) or a non-volatile memory (non-volatile memory), such as at least one disk storage. The memory 604 may optionally be at least one storage device located away from the aforementioned processor 601. The processor 601 may be combined with Figure 4In the described device, the memory 604 stores an application program, and the processor 601 calls the program code stored in the memory 604 to execute any of the above method steps.

[0058] The communication bus 602 may be a peripheral component interconnect (PCI) bus or an extended industry standard architecture (EISA) bus. The communication bus 602 may be divided into an address bus, a data bus, a control bus, etc. For ease of representation, Figure 4 Only one thick line is used in the diagram, but this does not mean that there is only one bus or only one type of bus.

[0059] Among them, the memory 604 may include a volatile memory (English: volatile memory), such as a random access memory (English: random-access memory, abbreviated: RAM); the memory may also include a non-volatile memory (English: non-volatile memory), such as a flash memory (English: flash memory), a hard disk drive (English: hard disk drive, abbreviated: HDD) or a solid-state drive (English: solid-state drive, abbreviated: SSD); the memory 604 may also include a combination of the above types of memory.

[0060] The processor 601 may be a central processing unit (CPU), a network processor (NP), or a combination of a CPU and a NP.

[0061] The processor 601 may further include a hardware chip. The hardware chip may be an application-specific integrated circuit (ASIC), a programmable logic device (PLD), or a combination thereof. The PLD may be a complex programmable logic device (CPLD), a field-programmable gate array (FPGA), a generic array logic (GAL), or any combination thereof.

[0062] Optionally, the memory 604 is also used to store program instructions. The processor 601 can call the program instructions to implement the repair method of the geopolymer repair material of the concrete structure as shown in the embodiment of the present application.

[0063] The embodiment of the present invention also provides a non-transitory computer storage medium, which stores computer executable instructions, and the computer executable instructions can execute the repair method of the geopolymer repair material of the concrete structure in any of the above method embodiments. Among them, the storage medium can be a disk, an optical disk, a read-only memory (ROM), a random access memory (RAM), a flash memory (Flash Memory), a hard disk (HDD) or a solid-state drive (SSD), etc.; the storage medium can also include a combination of the above types of memory.

[0064] Although the embodiments of the present invention have been described in conjunction with the accompanying drawings, those skilled in the art may make various modifications and variations without departing from the spirit and scope of the present invention, and such modifications and variations are all within the scope defined by the appended claims.

Claims

1. A geopolymer repair material for a concrete structure, characterized in that: The repair material is alkali activated slag fly ash, The raw materials include: sand, gravel, alkali activator, slag, fly ash, water, and each raw material is prepared according to weight to determine the alkali activated slag fly ash.

2. The repair material according to claim 1, characterized in that: The alkaline activator consists of water glass and sodium hydroxide.

3. The repair material according to claim 2, characterized in that: The modulus of the alkaline activator is 1.3, and the specific preparation quantities are: 147.2 parts of the water glass and 23.9 parts of the sodium hydroxide.

4. The repair material according to claim 2, characterized in that: The raw materials are prepared according to weight to determine the alkali activated slag fly ash, including: The alkali-activated slag fly ash is prepared in the proportion of 520 parts of sand, 965.5 parts of gravel, 250 parts of slag, 250 parts of fly ash, 147.2 parts of water glass, 23.9 parts of sodium hydroxide and 104.5 parts of water to improve the splitting tensile strength of the repair interface.

5. A method for repairing a concrete structure using a geopolymer repair material, characterized in that: include: Prepare the geopolymer repair material for concrete structure as described in any one of claims 1 to 4; Perform artificial regular roughening on the interface of the concrete to be repaired to determine the target repair interface; The repair material is applied at the target repair interface to repair the concrete to be repaired.

6. The method according to claim 5, characterized in that The roughening process is performed to expose the coarse aggregate to a depth of about 1 / 3 of its diameter.